The Pattern Of Travel Decisions And Tourist Expenditures For Local Tourism Revenue In Wonosobo Regency - Haniek Listyorini; Arif Rahman Hakim; Esti Agriyani Bawaulu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Every tourism destination wants sufficient economic impact from tourists visit and tourist expenditure for the destination. In fact, each region has set revenue targets for both the number of visitors and amount of various tourist expenditures. However, it is often found that not all of these revenue targets are met. Therefore, this research conducts a comprehensive study on tourist profile, travel decision and the amount of tourist expenditure with the case in Wonosobo Regency. In this study, quantitative research methods is used. Data collected by survey to 100 visitors in several tourist attractions, accommodation and local restaurants. The data is processed using SPSS and display in descriptive statistics. The result of this research found that tourist profile mostly come from Java Island, male gender, tend to be young in age, graduate from hinger education, middle-lower income level. Tourists utilize various sources information but dominantly by social media, with primary visit purpose for holidays, many repeaters tourist, in average visit for one day, able to reach 4-5 attractions, and the most popular attractions are Si Kunir Hills and Arjuna Temple Complex. There are 8 types of tourist expenditures that can provide tourism income opportunities for the region, include accommodation, food and drink, transportation, attraction tickets, services at travel agents, tourist attraction tickets, souvenirs. Amongst 8 types of tourist expenditures, the main expenditure component for one day tourist is buying souvenir or gift, but for 2 days tourist is spending for accommodation.